2019
DOI: 10.1002/jsde.12268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Surface Activity, Thermodynamic Parameters, and Performance Evaluation of Branched Carboxylate Gemini Surfactants

Abstract: Three novel carboxylate gemini surfactants (3CntaDA, n = 8, 10, and 12) were synthesized by two simple steps, and their structures were characterized using FT‐IR and 1H NMR. The surface activities of these surfactants were obtained from surface tension measurements at different temperatures, and the surface parameters containing the critical micelle concentration (CMC), surface tension (γ), minimum surface area per molecule ( Amin), and maximum surface excess concentration ( Γmax) were obtained from surface te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The explanation behind this trend can be credited to the higher hydrophobicity of C 16 -E2O2-C 16 because more hydrophobic gemini surfactants form more viscous solutions. It can be demonstrated that the synthesized cationic gemini surfactants have better emulsifying efficiency than previously synthesized gemini surfactants (Gawali and Usmani, 2020;Xie et al, 2019).…”
Section: Emulsifying Stabilitymentioning
confidence: 88%
“…The explanation behind this trend can be credited to the higher hydrophobicity of C 16 -E2O2-C 16 because more hydrophobic gemini surfactants form more viscous solutions. It can be demonstrated that the synthesized cationic gemini surfactants have better emulsifying efficiency than previously synthesized gemini surfactants (Gawali and Usmani, 2020;Xie et al, 2019).…”
Section: Emulsifying Stabilitymentioning
confidence: 88%
“…The foam rupture is mainly because the liquid film separating the gas becomes thinner from the thick, so the stability of the foam is related to the strength of the formed gas-liquid film. In general, the stronger the hydrophobic effect of surfactant molecules, the more tightly they are adsorbed on the liquid membrane, and the better the stability of foam is [44,54]. As shown in the figure, the foaming concentration of CnEO-5 gradually increases with increasing concentration, and when it reaches the critical micelle concentration, it no longer significantly increases.…”
Section: Foam Performancementioning
confidence: 93%
“…Generally speaking, the ratio of fluorescence intensity (I1/I3) is highly sensitive to the polar environment in which pyrene molecules (py) are located [4,44]. Therefore, the self-assembly behavior of CnEO-5 molecules in aqueous solutions can be studied by steadystate fluorescence probe method.…”
Section: Micropolaritymentioning
confidence: 99%
“…ΔS mic (kJ mol À 1 K À 1 ) SDDO 0.605 [78] 1.930 [79] 0.352 [79] 0.311 [79] 25 25 [80] 0.250 [80] 0.235 [80] 25 25 [81] 0.562 [81] [82] 25 Tensiometry -----À 43.26 -13.13 0.090 3 C 10 -DS 0.410 [83] 25 Tensiometry 27.60 -2.53 1.66 1.01 ----18-3-18 16-3-16 14-3-14 0.438 [84] 0.466 [84] 0.499 [84] 25. ChemistrySelect amine diacetate.…”
Section: Anionic Gemini Surfactantsmentioning
confidence: 99%
“…Carboxylate-based anionic geminis, viz., sodium salt of diethylenetriamine-N,N',N''-trialkyl-N,N'-dicarboxyl acid (3C n taDA) was synthesized [79] as shown in Scheme 17. Authors first synthesized sodium salts of diethylenetriamine-N,N'-dicarboxyl acid, intermediate product, by reacting diethylenetri-Scheme 15.…”
Section: Anionic Gemini Surfactantsmentioning
confidence: 99%